Efecto de las políticas tributarias implementadas en el periodo 2000-2012 en el nivel de actividad económica del Ecuador - Cueva Suárez, Daniela Alejandra (2014)
In 2000-2012, at least one tax reform has been made every year in Ecuador. However, while taxes have risen, GDP has also grown. This apparently contradicts economic theory, which establishes that a higher tax burden has negative effects on economic growth, since it affects individuals’ disposable income, thus reducing their capacity to consume. This research estimates an econometric model using major components from both aggregate supply and aggregate demand, to evaluate the effect of the latest tax reforms (2007-2012) in Ecuadorian economic growth...